A reforma do ensino médio: análise crítica acerca da elaboração e implementação da Base Nacional Comum Curricular no Estado do Maranhão - RODRIGUES, Paula Roberta Coutinho (2021)
The High School Reform through the Law and the reforms undertaken by the Common National Curriculum Base are the study objects of this paper. The motivation for this research was the possibility of reflecting on High School, considering the importance that this level of Basic School Education has in human development, in addition to the intrinsic relationship with the constantly changing world of work. The objective is critically reflect on the "new" High School curricular reform, highlighting the correlation of forces within the State and organized society, in the process of preparation, approval and execution of the Common National Curriculum Base, whose empirical reference for analysis is the Maranhão State Public Education System, through the actions of the State Department of Education - SEDUC, with a view to implementing this curriculum reference in public schools. The research reflections result, methodologically, from a theoretical foundation based on the historical materialist dialectic as a guide to a researcher's posture or worldview regarding the phenomenon to be studied; and chooses the theoretical aspect of Historical-Critical Pedagogy as a fundamental basis for the interpretation of this object of study. During this study, the following categories of analysis were chosen: Human Education, High School, Curriculum and Pedagogical Competences, with a view to revealing the foundations for the preparation and approval of the Common National Curriculum Base for the "new" High School and to seek the necessary mediations to answer the questions that instigate us. This path contributed to clarifying the conceptions of training contained within the scope of the corresponding legislation and the investigation into the process of implementing the Common National Curriculum Base for High Schools in the Maranhense Public Network, which is limited due to the worldwide context of the covid-19 pandemic. For this purpose, the consultation of official bibliographic and documental sources, including Law No. 13.415/2017 and the document of the Common National Curriculum Base (BRASIL, 2018), the complementary documents related to the Training Itineraries (BRASIL, 2018) and the Implementation Guide for the Common National Curriculum Base: guidelines for the Common National Curriculum Base – 2018 implementation process; New Secondary Education Implementation Guide – 2019, published by the MEC in partnership with the National Council of Secretaries of Education (CONSED) and the National Union of Municipal Education Directors (UNDIME) were essential to unveil the content of the current reforms. Within the scope of civil society, the publications of class representations (motions, letters, manifestos) and texts on the analysis of the Common National Curriculum Base that contributed to the identification of resistance stand out. These references were confronted by the production of literature about High School and the Curriculum by Competences established by the Common National Curriculum Base, thus, the studies by Nereide Saviani (1994) Malanchen (2013; 2014; 2016); Ramos (2001; 2004), Frigotto (2004; 2017); Kuenzer (1989; 1997; 2002; 2010; 2011; 2016; 2017), Ciavatta (2004), Saviani (2003; 2004; 2007; 2008; 2010), Duarte (2017) and others contributed to identifying the multiple determinations of the object of study. From an empirical point of view, this was manifested as a concrete reality in the implementing reform process in Maranhão. Thus, there was an uncritical adhesion by the Educational State Department, under the advice of think tanks in service of capitalist interests, to the Common National Curriculum Base. It is understood that the possibilities for analyzing this object have not been exhausted, since the adoption of this curricular model by schools is in progress, requiring further studies and new research questions. It is hoped that this study can contribute to problematize the process of implementing the High School reform in the context of education networks and support the action of teachers, contrary to business pedagogies.